INTRODUCING AQUAPONIC AS THE URBAN FARMING MODEL FOR STUDENT'S KNOWLEDGE: PENGENALAN AKUAPONIK SEBAGAI MODEL PERTANIAN PERKOTAAN UNTUK PENGETAHUAN SISWA - Hanum Isfaeni; Naufal Ma'arif; Muhammad Zaki Ananda; Sayyid Izzudin Muslimin; Reza Dino Mahardika; Galang Adi Fathriko (Universitas Airlangga, 2024)
The introduction of aquaponics through interesting learning media is expected to instill good knowledge in students about aquaponics. Technological devices, plants and animals in the aquaponic system which are used as learning media in several subjects or fields of study. One of the efforts in developing learning that attracts the interest and motivation of students is learning media. Learning media is one of the important learning components in the learning process, because learning media can increase students' interest and motivation in learning. The introduction of aquaponics as an interesting learning medium is expected to instill good knowledge in students (the younger generation), especially in the activities of developing modern agriculture or animal husbandry in urban areas. This activity was attended by 18 students and 1 accompanying teacher. Activities carried out through the method of discussion and demonstration (demonstration) of the aquaponic system.